2018
DOI: 10.3354/dao03201
|View full text |Cite
|
Sign up to set email alerts
|

Prominent hepatic ductular reaction induced by Oschmarinella macrorchis in a Hubbs’ beaked whale Mesoplodon carlhubbsi, with biological notes

Abstract: Beaked whales are among the least known group of cetaceans, and information regarding their pathology and parasitology is especially scarce. We describe a case of significant parasitism by a trematode found in the liver of an adult male Hubbs' beaked whale Mesoplodon carlhubbsi that stranded in Hokkaido, Japan. Post-mortem examinations revealed a localised area of discolouration restricted to the hilar region of the left hepatic lobe, where spindle-shaped trematodes occupied the dilated and hypertrophic bile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…With the present study, there is a possibility that the interspecies differences observed in the reactions of respective species may have been due to differences in the infecting trematode species: C. oblonga in the harbor and Dall's porpoises and O. macrorchis in the Hubbs' beaked whales. However, the two trematode species only differ morphologically by the presence of the lateral diverticula and are genetically very close (26). In fact, the genetic distance inferred from its mtND3 sequences between O. macrorchis and C. oblonga are closer than that between O. rochebruni within the same genus (26).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…With the present study, there is a possibility that the interspecies differences observed in the reactions of respective species may have been due to differences in the infecting trematode species: C. oblonga in the harbor and Dall's porpoises and O. macrorchis in the Hubbs' beaked whales. However, the two trematode species only differ morphologically by the presence of the lateral diverticula and are genetically very close (26). In fact, the genetic distance inferred from its mtND3 sequences between O. macrorchis and C. oblonga are closer than that between O. rochebruni within the same genus (26).…”
Section: Discussionmentioning
confidence: 97%
“…However, the two trematode species only differ morphologically by the presence of the lateral diverticula and are genetically very close (26). In fact, the genetic distance inferred from its mtND3 sequences between O. macrorchis and C. oblonga are closer than that between O. rochebruni within the same genus (26). Therefore, from both morphological and genetic perspectives, we presumed that the host response should naturally be alike.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For further characterization of the neoplastic lymphocytes, immunohistochemistry was performed on serial sections of the heart and hepatic peripheral nerve bundle according to a protocol described previously. 13 The antibodies used were as follows: monoclonal mouse antibody against CD3 (1:100, clone F7.2.38; Dako, Tokyo, Japan); polyclonal rabbit antibody against CD8 (1:200; Abcam, Tokyo, Japan); polyclonal rabbit antibody against granzyme B (1:400; Spring Bioscience, Pleasanton, CA); polyclonal rabbit antibody against CD20 (1:400; Thermo Fisher Scientific, Fremont, CA); monoclonal mouse antibody against CD79α (ready-to-use, clone JCB117; Dako); and polyclonal rabbit antibody against Pax5 (1:500; Thermo Fisher Scientific). Antigen retrieval involved microwave heat pretreatment at 97°C, for 15 min in citrate buffer solution (pH 6.0) for CD3, CD8, granzyme B, CD20, and Pax5, and in target retrieval solution (pH 6.1; Dako) for 20 min for CD79α.…”
mentioning
confidence: 99%